2014
DOI: 10.1038/tp.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor gene (NR3C1) methylation following stressful events between birth and adolescence. The TRAILS study

Abstract: Stress early in life is a known risk factor for the development of affective disorders later in life. Epigenetic mechanisms, such as DNA methylation, may have an important role in mediating that risk. Recent epigenetic research reported on the long-term relationship between traumatic stress in childhood and DNA methylation in adulthood. In this study, we examined the impact of various types of stress (perinatal stress, stressful life events (SLEs) and traumatic youth experiences) on methylation of the glucocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(131 citation statements)
references
References 52 publications
3
124
0
1
Order By: Relevance
“…However, for both NR3C1 and BDNF, maternal cortisol did not predict infant DNA methylation changes. Variation in DNA methylation within the NR3C1 1F region has been reported in both animal 15,18,19 and human [23][24][25][26][27] studies, suggesting that this epigenetic marker is developmentally sensitive to the quality of the environment. These studies have consistently reported increased DNA methylation of NR3C1 1F and our findings compliment previous reports examining the epigenetic impact of maternal depressed mood during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, for both NR3C1 and BDNF, maternal cortisol did not predict infant DNA methylation changes. Variation in DNA methylation within the NR3C1 1F region has been reported in both animal 15,18,19 and human [23][24][25][26][27] studies, suggesting that this epigenetic marker is developmentally sensitive to the quality of the environment. These studies have consistently reported increased DNA methylation of NR3C1 1F and our findings compliment previous reports examining the epigenetic impact of maternal depressed mood during pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…23 Increased NR3C1 1F DNA methylation has also been detected in DNA extracted from whole blood samples from young adolescents exposed to physical abuse in childhood, 24 and adolescents exposed to stressful life events or trauma. 25 This susceptibility to alterations in NR3C1 DNA methylation is also observed in response to prenatal distress. Increased NR3C1 1F DNA methylation has been found in cord blood of infants exposed to maternal depressed mood during pregnancy and this altered epigenetic state was predictive of stress responses in these infants at 3 months of age.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, another study has reported that there is a nonsignificant effect of perinatal stress, defined as the sum of maternal psychological problems during pregnancy or the 3 months after delivery, on NR3C1 methylation in adolescent offspring (van der Knaap et al, 2014). Incongruent findings on the methylation status of NR3C1 may be reflective of differences in methodologies or individual differences in the potential subsequent development of psychopathology in offspring.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Studies of early experiences in rats found that DNA methylation of the GR promoter region was altered by maternal care, which in turn was associated with GR expression and HPA responses to stress 12. In humans, stressful life events (e.g., trauma and abuse) have been associated with higher DNA methylation at the GR promoter region13, 14, 15, 16, 17, 18 as well as differential GR expression and biological markers of HPA‐axis activity, such as salivary cortisol 13, 14. Furthermore, GR methylation has been implicated in the development of PTSD following trauma 19.…”
Section: Introductionmentioning
confidence: 99%